Etiological Analysis and Targeted Management of Resistant Hypertension in a Cohort of 64 Chronic Kidney Disease Patients - Khan, Muhammad Zakir Hossain; Shieakh, S M Ibne; Dola, Fariha Tasnuva; Bhoumik, Sukhinath; Solayman, Mohammed (KYAMC Journal, 2026)
Background: Resistant hypertension (rHTN) is a common complication in chronic kidney disease (CKD) patients, often driven by identifiable secondary etiologies. Objectives: This study aimed to identify the prevalence of specific etiological factors in CKD patients with rHTN and evaluate the hemodynamic response one month after initiating targeted treatment. Materials and Methods: A prospective observational study was conducted on 64 CKD patients with rHTN. All patients were stabilized on a maximal regimen of amlodipine, prazosin, bisoprolol, and indapamide. They were screened and treated for hyperuricemia (febuxostat), secondary hyperparathyroidism (doxercalciferol), hyperprolactinemia (cabergoline), and renal artery stenosis. Blood pressure (BP) was reassessed after one month. Data were analyzed using descriptive statistics and a paired samples t-test in jamovi 2.6.44. Results: The prevalence of secondary factors was high: hyperuricemia 78.1% (n=50), secondary hyperparathyroidism 76.6% (n=49), and hyperprolactinemia 46.9% (n=30). Renal artery stenosis was confirmed in 3.1% (n=2). Targeted therapy led to a significant mean reduction in BP from 191.8/101.6 mmHg to 132.7/79.2 mmHg (mean reduction: -59.1/-22.4 mmHg, p<0.001). Conclusion: Resistant hypertension in CKD is frequently driven by treatable secondary factors. A systematic etiological workup followed by targeted intervention alongside conventional therapy leads to a profound improvement in BP control.